The petrography of staurolite-bearing garnet-gedrite-biotite-chlorite gneiss from the northeastern part of Akebono Rock in the Lützow-Holm Complex, East Antarctica - Kitano, Ippei; Hokada, Tomokazu; Baba, Sotaro; Kamei, Atsushi; Motoyoshi, Yoichi (2020)
The 11th Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences, Poster presentations, Mon. 16 Nov. - Fri. 18 Dec. conference object